2020
DOI: 10.4236/oalib.1106151
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Neural Networks and Deep Neural Networks Based on Intrusion Detection System

Abstract: The computer security has become a major challenge. Tools and mechanisms have been developed to ensure a level of compliance. These include the Intrusion Detection Systems (IDS). The principle of conventional IDS is to detect attempts to attack a network and to identify abnormal activities and behaviors. The reasons, including the uncertainty in searching for types of attacks and the increasing complexity of advanced cyber-attacks, IDS calls for the need for integration of methods such as Deep Neuron Networks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…It measures how well the model can identify true negative cases, indicating its capability to correctly classify non-intrusive in-stances. The results obtained from the Dense Neural Network were consistent with those obtained by [6]. The DNN model demonstrates good performance in terms of specificity and sensitivity for most classes, except for the R2L class where the sensitivity is 0 and an overall accuracy of 0.977.…”
Section: Discussion Of Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…It measures how well the model can identify true negative cases, indicating its capability to correctly classify non-intrusive in-stances. The results obtained from the Dense Neural Network were consistent with those obtained by [6]. The DNN model demonstrates good performance in terms of specificity and sensitivity for most classes, except for the R2L class where the sensitivity is 0 and an overall accuracy of 0.977.…”
Section: Discussion Of Resultssupporting
confidence: 82%
“…One significant advantage of dense neural networks in IDS is their ability to learn complex patterns and relationships from large-scale network data. Zarai, R. et al [6] conducted an experimental study and reported that a dense neural network architecture achieved an accuracy of 94% in detecting various types of network intrusions, outperforming traditional rule-based IDS approaches. Furthermore, the application of deep learning techniques, including the combination of convolutional neural networks (CNN) and dense neural networks, has demonstrated encouraging outcomes in Intrusion Detection Systems (IDS).…”
Section: Ids In Dnn and Rbfnnmentioning
confidence: 99%
“…The LM-BP neural network model was applied to an intrusion detection system, and the intrusion detection flow under LM-BP algorithm was given. Zarai et al [8] proposed an intrusion detection system based on deep neural network and short-term memory artificial neural network. Li [9] proposed a malicious attack detection method for IoT based on clustering and classification.…”
Section: Introductionmentioning
confidence: 99%